Statistical biases of spectral analysis with the ON-OFF likelihood statistic - Jouvin, L.; Lemière, A.; Terrier, R.; Ohm, S.; Oya, I.; van Eldik, Christopher (34th International Cosmic Ray Conference (ICRC2015), 2015)
Spectral extraction in data from ground-based gamma-ray observations is usually performed using the on-off likelihood statistic which is based on the profile likelihood technique. The latter is known to lead to inconsistent estimators in some situations. We present here a systematic Monte Carlo study of the distribution of fitted spectral parameters for typical observations with VHE (very high energy; >100GeV) observatories and show that in some conditions spectral extraction yields inconsistent estimators. We discuss some techniques to alleviate this effect and the impact on the search for spectral cutoffs in the very low statistic regime.